Analisis Makna Mu’min, Kafir dan Munafiq dalam Surat al-Baqarah Perspektif Tafsir al-Ibriz Karya KH. Bisri Musthafa - Durrotun Nashihah; Anshori . (Journal of Islamic Civilization, 2021)
The terms believer, infidel and hypocrite, are types of humans in believing in the truth, these three qualities cannot be measured and cannot be seen, therefore explanations of these characteristics are needed, in this case the interpretation that will be used as a source of discussion is local interpretation. Javanese-speaking Indonesian. the type of research used is a literature study, in this study is the interpretation of al-Ibrīz with the interpretation of the Java-Pegon model, from the interpretation of the Java-Pegon will be analyzed using interactive data, the purpose of this discussion, in addition to preserving the interpretation with local Javanese culture also opens opportunities for understanding, other perspectives or new perspectives on these three traits.   Istilah Mukmin, kafir dan munafik, merupakan jenis manusia dalam Istilah Mukmin, kafir dan munafik, merupakan jenis manusia dalam mempercayai kebenaran, ketiga sifat ini tidak bisa diukur dan tidak bisa terlihat, oleh sebab itu dibutuhkan penjelasan-penjelasan sifat-sifat tersebut, dalam hal ini tafsir yang kan digunakan sebagai sumber pembahasan adalah tafsir lokal Indonesia yang berbahasa Jawa. jenis penelitian yang digunakan adalah studi kepustakaan, dalam kajian ini ialah tafsīr al-Ibrīz dengan penafsiran model Jawa-Pegon, dari penafsiran Jawa-Pegon tersebut nantinya akan dianalisis menggunakan data interaktif, tujuan dari pembahasan ini, selain pelestarian tafsir dengan budaya lokal jawa juga membuka peluang adanya pemahaman, perpektif lain atau perpektif baru terhadap ketiga sifat tersebut.